Energy absorption of single and multi-cell profiles under bending load considering damage evolution - Estrada, Quirino (2018)
In this paper, the energy absorption response of single and multi-cell profiles with different cross sections under bending load is presented. Emphasis was given to the modeling of damage initiation criteria and damage evolution. For this purpose, several discrete models of thin-walled structures were developed using Abaqus/Explicit. To obtain reliable results, a numerical study of a double-chambered profile under quasi-static three-point bending was conducted and validated experimentally. The studied structures included profiles with triangular, square, hexagonal, and circular cross-sectional shapes. The beams were fabricated with aluminum alloy EN AW-7108 T6 and modeled with ductile, shear, and Müschenborn-Sonne forming limit diagram damage initiation criteria. From the numerical results, both single and multi-cell profiles show an improvement in crashworthiness performance as their cross sections tend to approach a circle. In this way, an improvement of up to 80.95% in the crush force efficiency (CFE) parameter was obtained. Similarly, the introduction of ribs allowed for an increase in the energy absorption performance of the profiles relative to the single structure (non-ribbed). In this sense, an increase in specific energy absorption (SEA) and CFE values of up to 40% and 69% was calculated. Relative to single profiles, a maximum resistance to bending and an increase in energy absorption are observed when the circular cross section is reinforced in the longitudinal and transverse directions. Finally, with the improvements found, the design of an impact door beam used in the automobile industry is presented and discussed.